Dantrolene for cerebral vasospasm after subarachnoid haemorrhage: a randomised double blind placebo-controlled safety trial. Issue 9 (24th October 2014) - Muehlschlegel, Susanne; Carandang, Raphael; Hall, Wiley; Kini, Nisha; Izzy, Saef; Garland, Bridget; Ouillette, Cynthia; van der Bom, Imramsjah M J; Flood, Thomas F; Gounis, Matthew J; Weaver, John P; Barton, Bruce; et al.
Abstract : Background: Dantrolene is neuroprotective in animal models and may attenuate cerebral vasospasm (cVSP) in human aneurysmal subarachnoid haemorrhage (aSAH). We evaluated safety, feasibility and tolerability of intravenous dantrolene (IV-D) in patients with aSAH. Methods: In this single-centre, randomised, double blind, placebo-controlled trial, 31 patients with aSAH were randomised to IV-D 1.25 mg every 6 h for 7 days (n=16) or equiosmolar free water/5% mannitol (placebo; n=15). Primary safety end points were incidence of hyponatraemia (sNa≤132 mmol/L) and liver toxicity (proportion of patients alanine transaminase, aspartate aminotransferase and AlkPhos >5× upper-limit-of-normal). Secondary end points included tolerability, systemic hypotension and intracranial hypertension. Efficacy was explored for clinical/radiological cVSP, delayed cerebral ischaemia (DCI), and 3-month functional outcomes. Quantitative analyses of angiograms and daily transcranial Doppler (TCD) were performed. Results: Between IV-D versus placebo, no differences were observed in the primary outcomes (hyponatremia 44% vs 67% (p=0.29); liver toxicity 6% vs 0% (p=1.0)). Three patients in the IV-D versus two in the placebo group had severe adverse events possibly attributable to infusion and reached stop criteria: one IV-D patient developed liver toxicity; two patients in each group developed brain oedema requiring osmotherapy. The majority of adverse events were not related to infusion (17 vs 5 (RR 2.2; 95% CI 0.7 to 6.7; p=0.16) in IV-D vs placebo). No differences in any categorical cVSP outcomes, DCI, 3-month outcomes or quantitative angiogram and TCD analyses were seen in this small safety trial not powered to detect efficacy. Conclusions: In this small trial, IV-D after aSAH was feasible, tolerable and safe. Trial registration number: http://clinicaltrials.gov NCT01024972 .